A Study on the Dynamic Interaction between Three-Axle Vehicle and Continuous Girder Bridge with Consideration of Braking Effects. (15th March 2017) - Nguyen, Xuan-Toan; Tran, Van-Duc; Hoang, Nhat-Duc
Abstract : Continuous girder bridges become increasingly popular because of the rapid development of highway throughout the world. Most of previous researches on vibration analysis of a multispan continuous bridge subject to complex traffic loading and vehicle dynamic interaction focus on the girder displacement not considering braking effects. In current literature, few studies have discussed the effects of braking on continuous girder bridges. In this study, we employ the finite element method (FEM) to investigate the dynamic response of continuous girder bridge due to three-axle vehicle. Vertical reaction forces of axles that change with time make bending vibration of girder increase significantly. The braking in the first span is able to create response in other spans. In addition, the dynamic impact factors are investigated by both FEM and experiments on a real bridge structure. The results of this study extend the current understanding of the bridge dynamic behaviors and can be used as additional references for bridge codes by practicing engineers.